The Legality of the USA s Use of Force to Counter Terrorism - Maher, Kiera (Department of Public Law, 2024)
The United States of America (“USA”) has often resorted to the use of force as a means to counter terrorism citing the right to use force in self-defence as the justification for it. A history of the USA's use of force against other states in the name of countering terrorism portrays that the country has often gone too far opening up the narrow exceptions to the prohibition on the use of force in the United Nations Charter and disregarding the fundamental requirements that must be met before using force in international law. This is evinced in the actions of the USA after the 9/11 attacks. After the events of 9/11, Bush declared that the USA was at war and then enacted drastic state responses to counter terrorism, including the use of military force. The legality of this has been challenged. This dissertation will assess the lawfulness of the USA's use of force against states to combat terrorism. It is hoped that this paper will contribute towards a clearer framework on the use of force in international law, specifically in the context of countering terrorism.